A hierarchical phytosociology of the Greater Zandvlei area - Szöke, Tim (Department of Biological Sciences, 2017)
The Zandvlei Nature Reserve is to be expanded to form the Greater Zandvlei Estuary Nature Reserve and will encorporate a much greater area (250 more hectares). The Greater Zandvlei area was classified by means of Zurich Montpellier (Braun Blanquet) procedures. 60 relevés were used to create a hierarchical phytosociology using TWINSPAN and DCA-ordination analyses. 3 major community types were identified, which were then subdivided to reveal 6 community types important to future management: Moist Grassland/Wetland Disturbed Parkland, Dune Asteraceous Fynbos, Thicket/Shrub Mosaic, Rhus-Euclea Dune Thicket and Homogenous Patches. CCA-ordination indicates that the abiotic soil factors sampled (texture composition, pH, carbon content and visible disturbance) explain very little of the variation between the communities (r²=0.002). This phytosociology is provided as a tool for future research in the area, and it is hoped to assist in future management decisions regarding the newly founded GZENR.